2011
DOI: 10.5799/ahinjs.01.2011.04.0077
|View full text |Cite
|
Sign up to set email alerts
|

p-ANCA and c-ANCA frequency and their relationship with other diseases in patients with lung cancer

Abstract: Objectives: In this study, we aimed to investigate the association of cancer with vasculitis and the frequency of cancer-related paraneoplastic syndromes and their relationship by measuring blood levels of Perinuclear type Anti-Neutrophilic Cytoplasmic Antibody (p-ANCA) and Cytoplasmic type antineutrophil cytoplasmic antibodies (c-ANCA) in patients with lung cancer and asthma and in healthy individuals. Materials and methods:20 patients diagnosed with asthma, 26 patients following up with a diagnosis of lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…This receptor is not only widely distributed in the respiratory tract, but also highly expressed in the kidney, liver, and digestive tract. [ 24 25 ] So the SARS-CoV-2 has the ability to replicate massively in the digestive system. In earlier studies, many teams found SARS-CoV-2 in feces of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This receptor is not only widely distributed in the respiratory tract, but also highly expressed in the kidney, liver, and digestive tract. [ 24 25 ] So the SARS-CoV-2 has the ability to replicate massively in the digestive system. In earlier studies, many teams found SARS-CoV-2 in feces of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Since the receptor used by the SARS-CoV-2 is the angiotensin-converting enzyme 2 (ACE2). This receptor is not only widely distributed in the respiratory tract, but also highly expressed in the kidney, liver, and digestive tract [24–25] . So the SARS-CoV-2 has the ability to replicate massively in the digestive system.…”
Section: Discussionmentioning
confidence: 99%
“…Akciğer kanseri ülkemizde en sık görülen (%17,6) kanser tipidir [6]. Elektrolit bozuklukları, böbrek-karaciğer ve çoklu organ yetmezliği, paraneoplastik sendromlar ve onkolojik acillerden olan uygunsuz ADH sendromu, kalp yetmezliği, tümör lizis sendromu, elektrolit bozuklukları, nörolojik komplikasyonlar ve medulla spinalis basıları komplikasyon olarak görülebilir [7][8][9][10]. Bu hastalıklarda da klinik benzer şekilde olup daha önceden tanı almamış ve acil servise bu şekilde getirilen hastalar olabilir.…”
Section: öZetunclassified